User interface considerations for telerobotics: The case of an agricultural robot sprayer - Adamides, George; Katsanos, Christos; Christou, Georgios; Xenos, Michalis; Papadavid, George; Hadzilacos, Thanasis (My University, 2014)
Agricultural robots can tackle harsh working conditions and hardness of work, as well as the shortage of laborers that is a bottleneck to agricultural production. Such robots exist, but they are not yet widespread. We believe that the limited usage of robotics in agriculture could be related to the fact that the mainstream direction for robotics in agriculture is full automation. The teleoperation of an agricultural robotic system can enable improved performance overcoming the complexity that current autonomous robots face due to the dynamic and unstructured agricultural environment. A field study was conducted to evaluate eight different user interfaces aiming to determine the factors that should be taken into consideration by designers while developing user interfaces for robot teleoperation in agriculture. Thirty participants, including farmers and agricultural engineers, were asked to use different teleoperation interaction modes in order to navigate the robot along vineyard rows and spray grape clusters. Based on our findings, additional views for target identification and peripheral vision improved both robot navigation (fewer collisions) and target identification (sprayed grape clusters). In this paper, we discuss aspects of user interface design related to remote operation of an agricultural robot. © 2014 SPIE.
Keywords: remote sensing; Robotics for agriculture; teleoperation; user interface design